Eliminate Theta Between The Equations
Here we will learn how to eliminate theta between the equations with the help of different types of problems.
Before we solve different types of question on eliminating θ (theta) let us understand what does it mean to "Eliminate theta from two or more equations"?
“Eliminate theta from two or more equations” means that the two or more equations are combined logically into one equation that it remains valid and theta (θ) does not appear in this new equation.
Worked-out examples to eliminate theta between the equations:
1. Eliminate theta between the equations:
q tan θ + p sec θ = x, p tan θ + q sec θ = y
Solution:
Squaring both sides of q tan θ + p sec θ = x we get,
(q tan θ + p sec θ)
^{2} = x
^{2} , …………….. (A)
Now, squaring both sides of p tan θ + q sec θ = y we get,
(p tan θ + q sec θ)
^{2} = y
^{2}, …………….. (B)
Now subtract (B) from (A) we get,
x
^{2} - y
^{2} = (q tan θ + p sec θ)
^{2} - (p tan θ + q sec θ)
^{2}
⇒ x
^{2} - y
^{2} = (q
^{2} tan
^{2} θ + p
^{2} sec
^{2} θ + 2qp tan θ sec θ) - (p
^{2} tan
^{2} θ + q
^{2} sec
^{2} θ + 2pq tan θ sec θ)
⇒ x
^{2} - y
^{2} = q
^{2} tan
^{2} θ + p
^{2} sec
^{2} θ + 2qp tan θ sec θ - p
^{2} tan
^{2} θ - q
^{2} sec
^{2} θ - 2pq tan θ sec θ
⇒ x
^{2} - y
^{2} = q
^{2} tan
^{2} θ - p
^{2} tan
^{2} θ + p
^{2} sec
^{2} θ - q
^{2} sec
^{2} θ
⇒ x
^{2} - y
^{2} = tan
^{2} θ (q
^{2} – p
^{2}) + sec
^{2} θ (p
^{2} - q
^{2})
⇒ x
^{2} - y
^{2} = - tan
^{2} θ (p
^{2} - q
^{2}) + sec
^{2} θ (p
^{2} - q
^{2})
⇒ x
^{2} - y
^{2} = sec
^{2} θ (p
^{2} - q
^{2}) - tan
^{2} θ (p
^{2} - q
^{2})
⇒ x
^{2} - y
^{2} = (p
^{2} – q
^{2}) (sec
^{2} θ - tan
^{2} θ)
⇒ x
^{2} - y
^{2} = (p
^{2} – q
^{2})(1), [Since sec
^{2} θ - tan
^{2} θ = 1]
⇒ x
^{2} - y
^{2} = p
^{2} – q
^{2}
Hence the required eliminant is x
^{2} - y
^{2} = p
^{2} - q
^{2}.
2. Eliminate theta between the equations: cos θ + sin θ = m and sec θ + csc θ = n.
OR,
If cos θ + sin θ = m and sec θ + csc θ = n, prove that n(m
^{2} – 1) = 2m.
Solution:
Given sec θ + csc θ = n ………………… (A)
⇒ 1/cos θ + 1/sin θ = n
⇒ (sin θ + cos θ)/cos θ sin θ = n
cos θ sin θ = (sin θ + cos θ)/n
sin θ = m/n, [using (A)] ………………… (B)
Now cos θ + sin θ = m
⇒ (cos θ + sin θ)
^{2} = m
^{2}
⇒ cos
^{2} θ + sin
^{2} θ + 2 sin θ cos θ = m
^{2}
⇒ 1 + 2 sin θ cos θ = m
^{2}
⇒ 1 + 2 ∙ (m/n) = m
^{2}, [Using (B)]
⇒ 2 (m/n) = m
^{2} - 1
⇒ 2m = n(m
^{2} - 1),
[Proved]
The above problems to eliminate theta between the equations are explained step-by-step so, that students get the clear concept how the equations are logically combined and it remains valid without the theta (θ) in the new equation.
● Trigonometric Functions
10th Grade Math
From Eliminate Theta Between the Equations to HOME PAGE
Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.